STRATEGI PENGELOLAAAN DESTINASI ECO-WISATA BERBASIS MASYARAKAT DI DANAU RANAU KECAMATAN LUMBOK SEMINUNG KABUPATEN LAMPUNG BARAT PROVINSI LAMPUNG - Besar, Ibrahim; Riza F, Ahmad; Noviera, Fri Rejeki (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The development of the eco-tourism sector today is one of the sources of national income which has a direct impact on increasing national economic growth and has a direct impact on Regional Original Income. Therefore, the Government has an interest in planning tourism development, issuing tourism policies and making and enforcing regulations. he government's attention hopes that all eco-tourism assets, especially eco-tourism, can be maintained, preserved and developed The objectives that can be formulated in this research are as follows Strategy for preparing local communities in the Ranau Lake eco-tourism destination, Lumbok District, in developing community based ecotourism Examine the extent to which Lake Ranau eco-tourism has an influence in empowering local communities. The Lake Ranau eco-tourism distenation development model The Lake Ranau eco-tourism distenation development model involves local communities Benefits of Research Theoretically, this research is expected to contribute to the development of communication science, especially concepts, theories, methods and approaches in the study of communication science in general. and especially Development and Culture Communication, Business Communication in the study of developing eco-tourism destinations in the Lake Ranau area, Lumbok District, West Lampung Regency. Practical AspectsThis research is used as information and reference material for the development of philosophical thinking in communication science. readiness of local communities in Lumbok District to receive eco-tourists. So, this research is expected to provide additional information for the government to create innovations to create tourism development policy strategies based on community empowerment programs in West Lampung Regency in particular and Lampung Province in general. Data analysis methodology SWOT analysis seeks to understand the communication behavior of the eco-tourism destination community through the views of the perpetrators